Hydrated salt phase change gel material, wearable device and preparation method

By using hydrated salt phase change gel materials in wearable devices, the problems of poor thermal conductivity and low heat storage density of the equipment in extreme environments are solved, and higher safety and comfort are achieved, and the uniformity of temperature distribution is improved through improved material structure.

CN119842367AActive Publication Date: 2025-04-18SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202510028965.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing wearable devices have problems such as poor thermal conductivity, low heat storage density, and discomfort in extreme environments. Traditional hydrated salt phase change materials are prone to phase separation and leakage problems during solid-liquid phase change.

Method used

Using hydrated salt phase-change gel material, by introducing a large number of hydrophilic groups into the gel network, the hydrated salt is adsorbed by hydrogen bonds and electrostatic interactions, preventing its leakage and achieving uniform distribution, thereby improving safety.

Benefits of technology

Improve the safety of the equipment, enhance flexibility and elasticity, make it more comfortable to wear, and improve thermal conductivity by adding conductive thermal fillers to achieve a more uniform temperature distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842367A_ABST
    Figure CN119842367A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wearable equipment, and particularly relates to a hydrated salt phase change gel material, a preparation method thereof, wearable equipment and a preparation method thereof. The hydrated salt phase change gel material provided by the invention is prepared from the following raw materials in percentage by mass: 30 to 97.7 percent of hydrated salt, 1 to 40 percent of gel monomer, 0 to 20 percent of conductive and heat-conducting filler, 0.1 to 5 percent of cross-linking agent, 0.1 to 5 percent of initiator, 0 to 40 percent of high polymer material, 0 to 10 percent of nucleating agent, 0.05 to 2.5 percent of additive and 0 to 40 percent of water. A gel network in the hydrated salt phase change gel material has a large number of hydrophilic groups, hydrated salt is adsorbed through hydrogen bonds and electrostatic interaction, leakage of the hydrated salt can be prevented, it can be guaranteed that the hydrated salt is evenly distributed in the gel network, phase separation is avoided, and use safety is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wearable devices, and in particular relates to a hydrated salt phase change gel material and a preparation method thereof, a wearable device and a preparation method thereof. Background Art

[0002] The human body regulates its body temperature through natural mechanisms, but in extreme environments (such as high temperature or severe cold), the body's self-regulation ability is limited, and long-term exposure may cause health problems or even endanger life. With the development of technology, wearable devices that assist in regulating human body temperature have emerged, but existing wearable devices (such as organic phase change temperature regulation collars) have problems such as poor thermal conductivity, low heat storage density, and discomfort when worn.

[0003] Hydrated salt phase change materials have become an alternative to organic phase change materials due to their advantages such as high heat storage density, good thermal conductivity, and flexible control of phase change temperature. However, traditional hydrated salt phase change materials are prone to phase separation and leakage problems during solid-liquid phase change, which limits their application in wearable devices. Summary of the invention

[0004] In view of this, the present invention provides a hydrated salt phase change gel material and a preparation method thereof, a wearable device and a preparation method thereof. The hydrated salt phase change gel material provided by the present invention has a large number of hydrophilic groups on the gel network, and adsorbs the hydrated salt through hydrogen bonds and electrostatic interactions, which can not only prevent the leakage of the hydrated salt, but also ensure that the hydrated salt is evenly distributed in the gel network, avoiding the occurrence of phase separation, thereby improving the safety of use.

[0005] In order to solve the above technical problems, the present invention provides a hydrated salt phase change gel material, comprising the following raw materials in percentage by weight:

[0006]

[0007]

[0008] Preferably, the hydrated salt includes one or more of sodium acetate hydrate, sodium sulfate hydrate, copper sulfate hydrate, magnesium sulfate hydrate, magnesium chloride hydrate, calcium chloride hydrate, zinc chloride hydrate, disodium hydrogen phosphate hydrate, sodium carbonate hydrate, lithium nitrate hydrate, magnesium nitrate hydrate, zinc nitrate hydrate, potassium aluminum sulfate hydrate and sodium thiosulfate hydrate.

[0009] Preferably, the gel monomer includes one or more of acrylamide, acrylamide derivatives, acrylic acid, acrylic acid derivatives, sodium acrylate, sodium acrylate derivatives, vinyl compounds, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide and maleic anhydride.

[0010] Preferably, the electrically conductive and thermally conductive filler comprises one or more of multi-walled carbon nanotubes, carbon nanofibers, expanded graphite, graphene oxide, graphene sheets, nanocarbon, nanoaluminum oxide, nanocopper oxide and nanoiron oxide;

[0011] The cross-linking agent includes N,N'-methylenebisacrylamide;

[0012] The initiator includes ammonium persulfate, potassium persulfate, α-ketoglutaric acid, 2,2-diethoxyacetophenone, 2-hydroxy-2-methylpropiophenone or 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone;

[0013] The polymer material includes one or more of gelatin, sodium alginate, agar, chitosan, hyaluronic acid, cellulose nanofibers, cellulose nanocrystals, bacterial cellulose, polyethylene glycol, polyvinyl alcohol, polyacrylic acid compounds and polyacrylamide compounds;

[0014] The nucleating agent includes one or more of sodium tetraborate, borax, strontium chloride hexahydrate, calcium sulfate dihydrate, nano aluminum nitride and sodium silicate nonahydrate;

[0015] The additives include one or more of an antibacterial agent, a fluorescent agent, a water-soluble pigment and a color-changing agent.

[0016] Preferably, the phase change temperature of the hydrated salt phase change gel material is -5 to 50°C, and the density is 1 g / cm 3 above.

[0017] The present invention also provides a method for preparing the hydrated salt phase change gel material described in the above technical solution, comprising the following steps:

[0018] Mixing raw materials except the initiator to obtain a mixed material;

[0019] The mixed material and the initiator are mixed and then subjected to a cross-linking reaction to obtain the hydrated salt phase change gel material.

[0020] Preferably, the cross-linking reaction is initiated by heating and / or ultraviolet light irradiation.

[0021] The cross-linking reaction time is 1 to 15 hours.

[0022] The present invention also provides a wearable device, comprising a hydrated salt phase change gel, a packaging material and an integrated module;

[0023] The hydrated salt phase change gel is the hydrated salt phase change gel material described in the above technical solution or the hydrated salt phase change gel material prepared by the preparation method described in the above technical solution.

[0024] Preferably, the packaging material includes thermoplastic polyurethane elastomer, polypropylene, polyethylene, polyethylene vinyl acetate, polyethylene terephthalate, nylon film, aluminum-plastic film or silica gel;

[0025] The integrated module includes an electric heating device and / or a sensor device;

[0026] The wearable device may be in the form of a collar, a vest, an insole, a waist protector, a knee pad or a helmet.

[0027] The present invention also provides a method for preparing the wearable device according to the above technical solution, comprising the following steps:

[0028] The integrated module is sandwiched between two layers of packaging materials and processed into a desired shape to obtain a primary wearable device;

[0029] Mixing raw materials except the initiator to obtain a mixed material;

[0030] The system obtained by mixing the mixed material and the initiator is loaded into the interlayer of the primary wearable device to carry out a cross-linking reaction, thereby obtaining a wearable device.

[0031] The present invention provides a hydrated salt phase change gel material, comprising the following raw materials in percentage by weight: 30-97.7% hydrated salt, 1-40% gel monomer, 0-20% conductive and thermal conductive filler, 0.1-5% cross-linking agent, 0.1-5% initiator, 0-40% polymer material, 0-10% nucleating agent, 0.05-2.5% additive and 0-40% water. There are a large number of hydrophilic groups on the gel network in the hydrated salt phase change gel material provided by the present invention, and the hydrated salt is adsorbed through hydrogen bonds and electrostatic interactions, which can not only prevent the leakage of the hydrated salt, but also ensure that the hydrated salt is evenly distributed in the gel network, avoid the occurrence of phase separation, and improve the safety of use. At the same time, the hydrated salt phase change gel material provided by the present invention has good flexibility and elasticity, so that it is more comfortable than pure phase change material (hydrated salt) while maintaining a stable shape. In addition, adding conductive and thermally conductive fillers during the preparation of hydrated salt phase change gel can improve thermal conductivity, make the temperature distribution inside the material more uniform, and improve the temperature comfort of wearing; according to the conductivity of the filler, an electric heating device can be combined to achieve rapid heating of the phase change gel. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A schematic diagram of a wearable vest prepared in Example 1;

[0033] Figure 2 The DSC curve of the phase change gel in the wearable vest prepared in Example 1;

[0034] Figure 3 A schematic diagram of a wearable waist protector prepared in Example 2;

[0035] Figure 4 A schematic diagram of a wearable collar prepared in Example 4; Figures 1 to 3 The middle filling site represents the filling position of the hydrated salt phase change gel;

[0036] Figure 5 The DSC curve of the phase change gel in the wearable collar prepared in Example 4;

[0037] Figure 6 The human body thermal management temperature curve of the wearable collar prepared in Example 4;

[0038] Figure 7 This is the DSC curve of the phase change gel in the wearable collar prepared in Example 5;

[0039] Figure 8 These are the leakage test results of the phase change gels prepared in Examples 1 to 5. DETAILED DESCRIPTION

[0040] The present invention provides a hydrated salt phase change gel material, comprising the following raw materials in percentage by weight:

[0041]

[0042] In terms of mass percentage, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 30-97.7% hydrated salt, which can be 40-80%, or 50-70%. As a specific embodiment of the present invention, the hydrated salt can include one or more of sodium acetate hydrate, sodium sulfate hydrate, copper sulfate hydrate, magnesium sulfate hydrate, magnesium chloride hydrate, calcium chloride hydrate, zinc chloride hydrate, disodium hydrogen phosphate hydrate, sodium carbonate hydrate, lithium nitrate hydrate, magnesium nitrate hydrate, zinc nitrate hydrate, potassium aluminum sulfate hydrate and sodium thiosulfate hydrate, and can also be sodium acetate trihydrate, sodium sulfate nonahydrate, sodium sulfate decahydrate, copper sulfate pentahydrate, magnesium sulfate dihydrate, magnesium sulfate pentahydrate, magnesium sulfate heptahydrate, hexahydrate, sodium acetate trihydrate, sodium sulfate nonahydrate, sodium sulfate decahydrate, copper sulfate pentahydrate, magnesium sulfate dihydrate, magnesium sulfate pentahydrate, magnesium sulfate heptahydrate, magnesium sulfate hexa ... The hydrated magnesium chloride, calcium chloride dihydrate, calcium chloride tetrahydrate, calcium chloride hexahydrate, zinc chloride tetrahydrate, disodium hydrogen phosphate dihydrate, disodium hydrogen phosphate heptahydrate, disodium hydrogen phosphate dodecahydrate, sodium carbonate monohydrate, sodium carbonate heptahydrate, sodium carbonate decahydrate, lithium nitrate trihydrate, magnesium nitrate hexahydrate, zinc nitrate hexahydrate, one or more of potassium aluminum sulfate dihydrate and sodium thiosulfate pentahydrate, and specifically a mixture of sodium thiosulfate pentahydrate and sodium carbonate decahydrate, a mixture of disodium hydrogen phosphate dodecahydrate and sodium carbonate decahydrate, sodium sulfate decahydrate or calcium chloride hexahydrate.

[0043] In terms of percentage by mass, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 1 to 40% gel monomer, which may be 7 to 30%, or 9 to 20%. As a specific embodiment of the present invention, the gel monomer includes one or more of acrylamide, acrylamide derivatives, acrylic acid, acrylic acid derivatives, sodium acrylate, vinyl compounds, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide and maleic anhydride, which may specifically be acrylamide, acrylic acid or sodium acrylate. As a specific embodiment of the present invention, the acrylamide derivative may be N-isopropylacrylamide, methacrylamide or acrylamide azobenzene; the acrylic acid derivative may be methacrylic acid, acrylate, methacrylate or sodium acrylate; the vinyl compound may be N-vinyl pyrrolidone or N-vinyl formamide.

[0044] In terms of mass percentage, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 0-20% conductive and thermally conductive fillers, which may be 1-15%, or 5-13%. As a specific embodiment of the present invention, the conductive and thermally conductive fillers may include one or more of multi-walled carbon nanotubes, carbon nanofibers, expanded graphite, graphene oxide, graphene sheets, nanocarbons, nanoalumina, nanocopper oxide, and nanoiron oxide, which may be specifically expanded graphite, multi-walled carbon nanotubes, or nanoalumina. In the present invention, adding conductive and thermally conductive fillers during the preparation of the hydrated salt phase change gel can improve thermal conductivity, make the temperature distribution inside the material more uniform, and improve the temperature comfort of wearing; adding conductive and thermally conductive fillers can be combined with an electric heating device to achieve rapid heating of the phase change gel.

[0045] In terms of mass percentage, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 0.1-5% crosslinking agent, which may be 0.5-4%, or 1-3%. As a specific embodiment of the present invention, the crosslinking agent may include N,N'-methylenebisacrylamide.

[0046] In terms of mass percentage, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 0.1-5% initiator, which may be 0.5-4%, or 1-3%. As a specific embodiment of the present invention, the initiator may include ammonium persulfate, potassium persulfate, α-ketoglutaric acid, 2,2-diethoxyacetophenone, 2-hydroxy-2-methylpropiophenone, or 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

[0047] In terms of mass percentage, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 0-40% polymer materials, which can be 1-30%, or 5-20%. As a specific embodiment of the present invention, the polymer materials can include one or more of gelatin, sodium alginate, agar, chitosan, hyaluronic acid, cellulose nanofibers, cellulose nanocrystals, bacterial cellulose, polyethylene glycol, polyvinyl alcohol, polyacrylic acid compounds and polyacrylamide compounds, which can be specifically gelatin, sodium alginate, hyaluronic acid or polyethylene glycol. In the present invention, the polymer material is filled inside the gel network to improve the stability of the structure and the adsorption capacity of the hydrated salt through hydrogen bonds.

[0048] In terms of mass percentage, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 0-10% nucleating agent, which may be 1-8%, or 2-6%. As a specific embodiment of the present invention, the nucleating agent may include one or more of sodium tetraborate, borax, strontium chloride hexahydrate, calcium sulfate dihydrate, nano-aluminum nitride, and sodium silicate nonahydrate, which may be specifically borax or sodium tetraborate. In the present invention, the nucleating agent can reduce the supercooling of the hydrated salt.

[0049] In terms of mass percentage, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 0.05-2.5% additives, which may be 0.1-2%, or 0.6-1%. As a specific embodiment of the present invention, the additives may include one or more of an antibacterial agent, a fluorescent agent, a water-soluble pigment, and a color-changing agent, which may be specifically an antibacterial agent, a water-soluble pigment, or a color-changing agent. As a specific embodiment of the present invention, the antibacterial agent may include one or more of metal ions, graphene, and nano-metal oxides; the metal ions may be silver ions, gold ions, copper ions, or zinc ions; the nano-metal oxides may be zinc oxide nanoparticles, titanium oxide nanoparticles, magnesium oxide nanoparticles, or iron oxide nanoparticles.

[0050] As a specific embodiment of the present invention, the fluorescent agent may include one or more of stilbene derivatives, coumarone derivatives and phthalimide derivatives.

[0051] As a specific embodiment of the present invention, the water-soluble pigment may include azo derivatives and / or natural pigments. As a specific embodiment of the present invention, the azo derivative may be Congo red, Sudan red, Disperse Yellow EG, Direct Lake Blue 6B or Acid Orange I, etc.; the natural pigment may be red yeast rice, chlorophyll, curcumin or carotene.

[0052] As a specific embodiment of the present invention, the color-changing agent may include one or more of metals, metal halides, metal oxides, polycrystals of metal oxides, vanadates, chromates, tungstates, Schiff bases, spirocyclics, dianthrone, α-naphthoquinone derivatives, polymers and liquid crystal materials; the metal may include Cu, Ag or Zn; the metal halide may be HgI, Ag2HgI4, Ti2HgI4 or Pb2HgI4; the metal oxide may be VO2, CoAl2O4, CoWO4, CoMoO4, CuMoO4 or NiMoO4; the polycrystal of the metal oxide may be PbO·Bi2O3·4Ta2O5; The vanadate may be BiVO4 or NaV3O8·1.5H2O; the chromate may be NH4Cr2O7 or CuCrO4; the tungstate may be Bi2WO6 or MnWO4; the Schiff base may be 2,3,3-trimethylspiropyran Schiff base; the spiro ring may be spiropyran or spiro[chromene-2,3'-dihydroindole]; the dianthrone may be dianthrone; the α-naphthoquinone derivative may be 2,3-naphthoquinone and 1,4-naphthoquinone; the polymer may be polydiyne, polysilane, polygermane or polythiophene; the liquid crystal material may be 4-cyano-4'-pentylbiphenyl, 4'-hexyl-4-biphenylnitrile or 4-butyl-4'-cyanobiphenyl.

[0053] In terms of mass percentage, the raw materials for preparing the hydrated salt phase change gel material provided by the present invention include 0-40% water, which can be 7-30%, or 10-20%. As a specific embodiment of the present invention, the water can be deionized water. In the present invention, when there is enough water in the hydrated salt, no additional water needs to be added.

[0054] As a specific embodiment of the present invention, the phase change temperature of the hydrated salt phase change gel material can be -5 to 50°C, or 15 to 40°C; the density of the hydrated salt phase change gel material can be 1g / cm 3 Above, can also be 2 ~ 3g / cm 3 .

[0055] The hydrated salt phase-change gel material provided by the present invention has high heat storage density and excellent thermal conductivity and is not prone to leakage.

[0056] The present invention also provides a method for preparing the hydrated salt phase change gel material described in the above technical solution, comprising the following steps:

[0057] Mixing raw materials except the initiator to obtain a mixed material;

[0058] The mixed material and the initiator are mixed and then subjected to a cross-linking reaction to obtain the hydrated salt phase change gel material.

[0059] The present invention mixes raw materials except the initiator to obtain a mixed material. As a specific embodiment of the present invention, the mixing can be adding raw materials except the initiator and the hydrated salt into the molten hydrated salt and stirring; the present invention has no special limitation on the stirring, as long as it can be mixed evenly. As a specific embodiment of the present invention, the hydrated salt is melted to obtain a molten hydrated salt. The present invention has special requirements on the melting temperature, and the conventional method in the art can be used.

[0060] After obtaining the mixed material, the present invention mixes the mixed material and an initiator and then performs a cross-linking reaction to obtain the hydrated salt phase change gel material. As a specific embodiment of the present invention, the mixing can be carried out under stirring conditions; the present invention has no special limitation on the stirring, as long as it can be mixed evenly. The system after mixing the mixed material and the initiator is a liquid with good fluidity, which can be poured into a mold of any shape to form a hydrated salt phase change gel material with a specific shape.

[0061] As a specific embodiment of the present invention, the initiation method of the cross-linking reaction may include heating and / or ultraviolet light irradiation; the heating temperature may be 50-80°C, or 60-70°C; the wavelength of the light source for ultraviolet light irradiation may be 365nm; the cross-linking reaction time may be 1-15h, or 5-12h.

[0062] The present invention only needs heating or ultraviolet light irradiation to initiate a cross-linking reaction. The gel formed after the cross-linking reaction is complete has good shape flexibility and elasticity, so that it is more comfortable than pure phase change materials while maintaining a stable shape.

[0063] The present invention also provides a wearable device, comprising a hydrated salt phase change gel, a packaging material and an integrated module;

[0064] The hydrated salt phase change gel is the hydrated salt phase change gel material described in the above technical solution or the hydrated salt phase change gel material prepared by the preparation method described in the above technical solution.

[0065] As a specific embodiment of the present invention, the packaging material may include thermoplastic polyurethane elastomer (TPU), polypropylene (PP), polyethylene (PE), polyethylene vinyl acetate (EVA), polyethylene terephthalate (PET), nylon film (PA), aluminum-plastic film or silicone; the integrated module may include an electric heating device and / or a sensor device, and the heating device may be an electric heating wire; the wearable device may include a collar, a vest, an insole, a waist protector, a knee pad or a helmet; the outermost layer of the wearable device may also be provided with a silicone sleeve layer.

[0066] The hydrated salt phase change gel provided by the present invention has good flexibility and elasticity. When a wearable device is worn using the hydrated salt phase change gel, it can easily fit the curve of the human body, thereby improving wearing comfort and freedom of movement. At the same time, the hydrated salt phase change gel provided by the present invention can maintain excellent flexibility and shape memory effect under different environmental conditions to adapt to the wearer's sports and activity needs.

[0067] The wearable device provided by the present invention is applicable to multiple fields such as sports and medical treatment.

[0068] The wearable device provided by the present invention has the advantages of a wide adjustable phase change temperature range, high heat storage density, good mechanical flexibility, etc., and can further expand its application field by integrating multifunctional modules (such as electric heating, sensors, etc.), and is suitable for fields such as temperature regulation, health monitoring and intelligent control.

[0069] The present invention also provides a method for preparing the wearable device described in the above technical solution, which may include the following steps:

[0070] The integrated module is sandwiched between two layers of packaging materials and processed into a desired shape to obtain a primary wearable device;

[0071] Mixing raw materials except the initiator to obtain a mixed material;

[0072] The system obtained by mixing the mixed material and the initiator is loaded into the interlayer of the primary wearable device to carry out a cross-linking reaction, thereby obtaining a wearable device.

[0073] The present invention has no special requirements on the processing method of the stacked packaging material, and the conventional method in the art can be used. As a specific embodiment of the present invention, the primary wearable device is provided with an opening for easy filling; after filling, the opening is sealed and closed.

[0074] The present invention encapsulates hydrated salts through the chemical cross-linking network of the gel, which has shape stability, good mechanical properties and high heat storage density. Compared with amorphous organic phase change materials, it is not easy to seep and leak, and the packaging cost is lower. The wearable device provided by the present invention has high energy storage density, less mass required to store the same energy, and has flexibility after melting and crystallization, which greatly improves the comfort of wearing; and the phase change temperature can be adjusted by changing the type of hydrated salt, and the phase change temperature adjustment range is 0 to 100°C, and can also be 20 to 50°C. Low phase change temperature can cool the human body in hot weather, and high phase change temperature can keep the human body warm in cold weather. The wearable device provided by the present invention can realize convenient and fast heating function for high phase change temperature materials suitable for winter use combined with electric heating devices. The wearable device provided by the present invention can also adjust the color through water-soluble pigments to improve aesthetics.

[0075] Wearable devices based on hydrated salt phase change gel have simpler preparation processes, more comfortable wearing experience, and a wider range of phase change temperature selection. The present invention uses a highly efficient and stable hydrated salt phase change gel material through the gelation technology of hydrated salt to develop a multifunctional smart wearable device suitable for different environments and human needs.

[0076] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0077] Example 1

[0078] The wearable vest based on phase change gel was prepared as follows:

[0079] Two sheets of thermoplastic polyurethane elastomer (TPU) with a thickness of 1 mm were hot pressed into Figure 1 The shape of the vest shown leaves a feed opening;

[0080] 100 g of sodium sulfate decahydrate, 2 g of borax, 10 g of acrylamide, 0.5 g of N,N'-methylenebisacrylamide, 2 g of gelatin, 10 g of deionized water and 1 g of Sudan red were stirred and mixed at 40° C. to obtain a mixed material;

[0081] Add 0.1 g of ammonium persulfate to the mixture, stir evenly, pour into the vest interlayer and seal it; store it in a 60°C environment for 12 hours for thermal cross-linking reaction to obtain a phase change gel wearable vest.

[0082] The wearable collar prepared in Example 1 was tested by differential scanning calorimetry to obtain a DSC curve, as shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the melting point of the hydrated salt (sodium sulfate decahydrate) phase change gel in the wearable collar is 33.3°C and the melting enthalpy is 148.0 kJ / kg.

[0083] Example 2

[0084] The wearable waist protector based on phase change gel was prepared as follows:

[0085] Use two pieces of 0.02mm thick aluminum-plastic film and heat press them into Figure 3 The shape of the waist guard shown has a feed opening;

[0086] 40 g of calcium chloride hexahydrate, 10 g of sodium tetraborate, 15 g of acrylic acid, 4 g of N,N'-methylenebisacrylamide, 20 g of sodium alginate, and 2 g of graphene were stirred and mixed at 40° C. to obtain a mixed material;

[0087] Add 1g of ammonium persulfate to the mixture, stir evenly, pour it into the waist protector interlayer and seal it, then put 2mm thick silicone on the outer layer; store it in a 70℃ oven for 12h to undergo cross-linking reaction to obtain a phase change gel wearable waist protector with antibacterial function.

[0088] Example 3

[0089] The phase change gel-based wearable insole was prepared as follows:

[0090] Two pieces of 1.5 mm thick silicone are used to prepare the shape of an insole, leaving a feed inlet and an electric heating wire inside;

[0091] 25 g of sodium thiosulfate pentahydrate, 5 g of sodium carbonate decahydrate, 15 g of sodium acrylate, 3 g of N,N'-methylenebisacrylamide, 15 g of hyaluronic acid, 5 g of deionized water and 1 g of an intelligent color-changing agent that changes from colorless to blue at 36°C are stirred and mixed to obtain a mixed material;

[0092] Add 0.06 g of ammonium persulfate to the mixture, stir evenly and pour into the insole interlayer pre-installed with electric heating wire. After sealing, store in a 60°C oven for 12 hours for cross-linking reaction to obtain a phase change gel wearable insole with electric heating function.

[0093] Example 4

[0094] The smart temperature monitoring phase change gel wearable collar was prepared as follows:

[0095] Two sheets of thermoplastic polyurethane elastomer (TPU) with a thickness of 0.05 mm were used, two temperature sensors were placed in the sandwich, and hot pressed into a Figure 4 The shape of the collar shown has a feed port, one temperature sensor in the middle to monitor the material temperature, and one below the middle where it contacts the skin.

[0096] 25 g of disodium hydrogen phosphate dodecahydrate, 5 g of sodium carbonate decahydrate, 15 g of sodium acrylate, 3 g of N,N'-methylenebisacrylamide, 10 g of polyethylene glycol, 5 g of deionized water and 1 g of a smart color-changing agent that changes from blue to red at 26°C are stirred and mixed to obtain a mixed material;

[0097] Add 0.02 g of α-ketoglutaric acid to the mixture, stir evenly, pour into a collar with a built-in temperature sensor and seal it; after irradiating it under ultraviolet light with a wavelength of 365 nm for 1 hour, put it in a 60°C oven and store it for 12 hours for cross-linking reaction to obtain a wearable collar with temperature monitoring function.

[0098] The wearable collar prepared in Example 4 was tested by differential scanning calorimetry to obtain a DSC curve, as shown in FIG. Figure 5 As shown. Figure 5It can be seen that the melting point of the composite hydrated salt phase change gel (disodium hydrogen phosphate dodecahydrate and sodium carbonate decahydrate) in the wearable collar is 24.8°C and the melting enthalpy is 143.2 kJ / kg.

[0099] The wearable collar prepared in Example 4 was placed in a refrigerator for 4 hours, taken out and worn on the neck. The temperature curve fed back by the temperature sensor during the process was as follows: Figure 6 The high enthalpy value of the hydrated salt phase change gel enables it to maintain a temperature range of 24-26°C for up to 80 minutes, which has a good human body thermal management effect.

[0100] Example 5

[0101] The high thermal conductivity phase change gel wearable collar was prepared as follows:

[0102] Two sheets of thermoplastic polyurethane elastomer (TPU) with a thickness of 0.05 mm were hot pressed into Figure 4 The shape of the collar shown leaves a feed opening;

[0103] 200 g of disodium hydrogen phosphate dodecahydrate, 140 g of sodium carbonate decahydrate, 20 g of acrylamide, 2 g of N,N'-methylenebisacrylamide, 5 g of deionized water and 8 g of nano-alumina were stirred and mixed to obtain a mixed material;

[0104] Add 0.4 g of α-ketoglutaric acid to the mixture, stir evenly, pour into the collar and seal it; irradiate under ultraviolet light with a wavelength of 365 nm for 1 hour, then store in a 60°C oven for 12 hours for cross-linking reaction to obtain a phase change gel wearable collar.

[0105] The wearable collar prepared in Example 5 was tested by differential scanning calorimetry to obtain a DSC curve, as shown in FIG. Figure 7 As shown. Figure 7 It can be seen that the melting point of the composite hydrated salt phase change gel (disodium hydrogen phosphate dodecahydrate and sodium carbonate decahydrate) in the wearable collar is 25.5°C and the melting enthalpy is 205.3 kJ / kg.

[0106] A leakage test was performed on the hydrated salt phase change gel prepared in Examples 1 to 5, specifically: first, the mixed material and initiator prepared in Examples 1 to 5 were poured into a mold of a specific shape for solidification to obtain a hydrated salt phase change gel with stable shape; the gel was placed on a piece of filter paper, and then placed in an oven at 80°C (a temperature higher than its melting point) for 2 hours, and the shape changes of the hydrated salt phase change gel before and after heating were compared, and the filter paper was observed to see if there were any signs of leakage. Figure 8 The hydrated salt phase change gel of each embodiment before and after heat preservation and the physical picture of the filter paper after heat preservation are shown in FIG. Figure 8It can be seen that after the hydrated salt phase change gel on the filter paper is heated to 80°C and kept warm, the shape of the material remains unchanged, and there is no material residue on the filter paper, indicating that the hydrated salt phase change gel is not prone to leakage. The flexibility and elasticity of the hydrated salt phase change gel provided by the present invention enable it to fit the curve of the human body, ensuring free movement and comfort when worn; at the same time, it can still maintain flexibility and shape memory effect under different environmental conditions, and adapt to various sports and activity needs of the wearer. The present invention can accurately change the phase change temperature by flexibly adjusting the type of hydrated salt to meet the cooling or heating needs in different environments. Multifunctional modules such as integrated electric heating devices and temperature sensors can not only adjust the wearer's body temperature in real time, but also support intelligent monitoring and control. They are widely used in sports, medical care, outdoor activities and other fields, showing broad application prospects and market potential.

[0107] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A hydrated salt phase change gel material, characterized in that: Including the following raw materials in percentage by weight:

2. The hydrated salt phase change gel material according to claim 1, characterized in that: The hydrated salt includes one or more of sodium acetate hydrate, sodium sulfate hydrate, copper sulfate hydrate, magnesium sulfate hydrate, magnesium chloride hydrate, calcium chloride hydrate, zinc chloride hydrate, disodium hydrogen phosphate hydrate, sodium carbonate hydrate, lithium nitrate hydrate, magnesium nitrate hydrate, zinc nitrate hydrate, potassium aluminum sulfate hydrate and sodium thiosulfate hydrate.

3. The hydrated salt phase change gel material according to claim 1, characterized in that: The gel monomer includes one or more of acrylamide, acrylamide derivatives, acrylic acid, acrylic acid derivatives, sodium acrylate, sodium acrylate derivatives, vinyl compounds, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide and maleic anhydride.

4. The hydrated salt phase change gel material according to claim 1, characterized in that: The conductive and thermally conductive filler includes one or more of multi-walled carbon nanotubes, carbon nanofibers, expanded graphite, graphene oxide, graphene sheets, nanocarbon, nanoaluminum oxide, nanocopper oxide and nanoiron oxide; The cross-linking agent includes N,N'-methylenebisacrylamide; The initiator includes ammonium persulfate, potassium persulfate, α-ketoglutaric acid, 2,2-diethoxyacetophenone, 2-hydroxy-2-methylpropiophenone or 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; The polymer material includes one or more of gelatin, sodium alginate, agar, chitosan, hyaluronic acid, cellulose nanofibers, cellulose nanocrystals, bacterial cellulose, polyethylene glycol, polyvinyl alcohol, polyacrylic acid compounds and polyacrylamide compounds; The nucleating agent includes one or more of sodium tetraborate, borax, strontium chloride hexahydrate, calcium sulfate dihydrate, nano aluminum nitride and sodium silicate nonahydrate; The additives include one or more of an antibacterial agent, a fluorescent agent, a water-soluble pigment and a color-changing agent.

5. The hydrated salt phase change gel material according to any one of claims 1 to 4, characterized in that: The phase change temperature of the hydrated salt phase change gel material is -5 to 50°C and the density is 1 g / cm 3 above.

6. The method for preparing the hydrated salt phase change gel material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing raw materials except the initiator to obtain a mixed material; The mixed material and the initiator are mixed and then subjected to a cross-linking reaction to obtain the hydrated salt phase change gel material.

7. The preparation method according to claim 6, characterized in that: The cross-linking reaction is initiated by heating and / or ultraviolet light irradiation. The cross-linking reaction time is 1 to 15 hours.

8. A wearable device, characterized in that: Including hydrated salt phase change gel, packaging materials and integrated modules; The hydrated salt phase change gel is the hydrated salt phase change gel material according to any one of claims 1 to 5 or the hydrated salt phase change gel material prepared by the preparation method according to claim 6 or 7.

9. The wearable device according to claim 8, characterized in that: The packaging material includes thermoplastic polyurethane elastomer, polypropylene, polyethylene, polyethylene vinyl acetate, polyethylene terephthalate, nylon film, aluminum plastic film or silica gel; The integrated module includes an electric heating device and / or a sensor device; The wearable device may be in the form of a collar, a vest, an insole, a waist protector, a knee pad or a helmet.

10. The method for preparing the wearable device according to claim 8 or 9, characterized in that: The following steps are involved: The integrated module is sandwiched between two layers of packaging materials and processed into a desired shape to obtain a primary wearable device; Mixing raw materials except the initiator to obtain a mixed material; The system obtained by mixing the mixed material and the initiator is loaded into the interlayer of the primary wearable device to carry out a cross-linking reaction, thereby obtaining a wearable device.

Citation Information

Patent Citations

  • Solid-solid phase change energy storage hydrogel with stable shape and preparation method thereof

    CN104817998A

  • Heat-conducting phase-change hydrogel and preparation method thereof

    CN116656071A

  • Phase-change hydrogel with flexibility in multiple temperature intervals as well as preparation method and application of phase-change hydrogel

    CN117924591A

  • Inorganic hydrated salt phase change gel material with photoresponse phase change as well as preparation method and application of inorganic hydrated salt phase change gel material

    CN118271514A

  • Hydrogel hydrated salt composite phase change material with low phase change temperature, preparation method of hydrogel hydrated salt composite phase change material and energy storage equipment

    CN118853091A

Cited By

  • Absorption and separation integrated nanofiber-based hydrated salt gel thermal protection material for lithium ion battery as well as preparation method and application of adsorption and separation integrated nanofiber-based hydrated salt gel thermal protection material

    CN120865849A

  • Hydrated salt phase change gel material, wearable device, and preparation methods

    WO2026148952A1